The Effect of Sub-Acute Inhalation Exposure to Polyethylene Micro-Nano Plastics on the Histopathological Features of the Mammary Glands in Female Wistar White Rats (Rattus Norvegicus) - Kusuma, Ihda Dian; Janasti, Laksmitha; Sari, Riana Trinovita; Nanda, Britania Laila; Sulistomo, Hikmawan Wahyu; Nurdiana, Nurdiana (JURNAL INFO KESEHATAN, 2024)
Most household appliances are made of plastic derived from synthetic petroleum and result from polymerization processes. One type of plastic is Polyethylene (PE). Polyethylene (PE) contains antimony trioxide compounds that are carcinogenic if ingested in excessive amounts, triggering cancer and oxidative stress. This effect can be assessed by measuring malondialdehyde (MDA) levels in the body. This study aims to determine the proliferation of abnormal cells in the lactiferous ducts and mammary gland acini, as well as the increase in MDA levels. The research method used is a true experimental design with a Randomized Post Test Only Group Design. This study used the mammary organs and blood of female white rats exposed to PE for 28 days. The number of samples used in this study was 12 female white rats. The results showed significant differences in the mammary glands' histopathological features and MDA levels. Based on the Independent T-Test results on the number of cell layers in the lactiferous ducts, acini, and the number of acini (p<0.05) and the Mann-Whitney test on MDA levels (p<0.05). Significant changes in the histopathological features and MDA levels were observed in the mammary glands exposed to polyethylene (PE) plastic. Exposure to micro-nano plastics of PE type at a dose of 15 mg/m3 for 28 days differed significantly in the MDA levels of mammary glands, histopathological picture of mammary glands at cell proliferation events, both in the lactiferous ducts and acini cells. In addition, exposure to PE plastic has the potential to cause health problems in the breast organs if exposed for a long time and in excess doses.